Impact of COVID-19 on vocal cord mobility: a case series study - Sameh M. Zamzam; Rania Gamal Hanafy (The Egyptian Journal of Otolaryngology, 2021)
Abstract Background The World Health Organization (WHO) has declared the pandemic of COVID-19 infection in March 2020, most of cases presented with mild symptoms, and a significant number of cases showed variable neurological pictures. Vocal cord paralysis with no clear cause is termed as idiopathic vocal cord paralysis and supposed to be caused by viral infection. This is a case series study; data were collected prospectively from patients presented to the ENT clinic of Kasr Alainy (Cairo university) and Railway hospitals. Patients presented with defective vocal cord movement with concurrently or recently passed COVID-19 infection were reported from March 2020 to April 2021. Results Authors have reported 6 cases of vocal cord paralysis mainly unilateral due to COVID-19 infection as an only clear cause within 14 months. Age ranges from 39 to 69 years, 2 males and 4 females. Patients presented with different clinical scenarios. Follow-up of the cases showed spontaneous recovery in 5 cases and one case underwent cord medialization. Conclusion Viral infection could be an underlying cause of idiopathic laryngeal cord paralysis; in the new era of the COVID-19 pandemic, physicians all over the world noticed variable neurological pictures; in this study, we presented 6 cases of vocal cord paralysis mainly unilateral supposed to be due to COVID-19 infection; all cases showed spontaneous recovery apart from one case that needed medialization of the cord.